IMMUNO DIAGNOSIS OF ENDOPHTHALMITIS BY DETECTING VITREOUS FLUID ANTIBODY USING ENZYME LINKED IMMUNOSORBENT ASSAY - GURU C. PATRA, (International Journal of Pharma and Bio Sciences, 2014)
The novelty of the method developed in the present study was the use of vitreous fluid as specimen for the indirect-ELISA. The indirect-ELISA was evaluated by using C. albicans whole cell antigen for the detection of IgG antibody in vitreous fluid of C. albicans endophthalmitis and control subjects. All these cases were considered with the confirmation of vitreous fluid culture for its more specificity in nature. The indirect-ELISA was given 94.64% of positivity result for the detection of anti-C. albicans antibody(IgG) in vitreous fluid. The test quality of indirect-ELISA was showed the sensitivity 91.44%, specificity 100%, efficiency 92.20%, PPV 100% & NPV 53.19%. The reasonable in its specificity and sensitivity for antibody detection in vitreous fluid than antibody detection in serum, the ELISA method developed here might be useful for diagnosis of endophthalmitis candidiasis.